2020
DOI: 10.1002/hep4.1515
|View full text |Cite
|
Sign up to set email alerts
|

Ritonavir and Lopinavir Suppress RCE1 and CAAX Rab Proteins Sensitizing the Liver to Organelle Stress and Injury

Abstract: Organelle stress and Liver injuries often occur in human immunodeficiency virus (HIV) infected patients underanti-HIV therapies, yet few molecular off-targets of anti-HIV drugs have been identified in the liver. Here, we found through total RNA sequencing that the transcription of a host protease Ras converting CAAX endopeptidase 1 (RCE1) was altered in HepG2 cells treated with anti-HIV protease inhibitors, ritonavir and lopinavir. Levels of RCE1 protein were inhibited in HepG2 and primary mouse hepatocytes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…In a more recent study evaluating the biliary excretion index (BEI) of 5( 6 )-carboxy-29, 79 dichlorofluorescein (CDF) through confocal imaging, the inhibitory effects of LPV was further supported ( 88 ). In another recent study, hepatotoxicity of PIs, LPV and, RTV, was reported to interfere with ER-Golgi trafficking via inhibition of Ras converting CAAX endopeptidase-1 (RCE1) and its potential substrates, leading to cellular stress responses and fatty liver disease ( 89 ). Another possible cause of hepatotoxicity due to LPV/RTV is insufficient P450 activity to metabolize large amounts of those drugs during the treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study evaluating the biliary excretion index (BEI) of 5( 6 )-carboxy-29, 79 dichlorofluorescein (CDF) through confocal imaging, the inhibitory effects of LPV was further supported ( 88 ). In another recent study, hepatotoxicity of PIs, LPV and, RTV, was reported to interfere with ER-Golgi trafficking via inhibition of Ras converting CAAX endopeptidase-1 (RCE1) and its potential substrates, leading to cellular stress responses and fatty liver disease ( 89 ). Another possible cause of hepatotoxicity due to LPV/RTV is insufficient P450 activity to metabolize large amounts of those drugs during the treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…Extraction of proteins from the whole-cell lysates, immunohistochemistry, and fluorescence immunohistochemistry were conducted according to the method described previously. (21,22)…”
Section: Real-time Polymerase Chain Reaction Immunoblotting and Analysismentioning
confidence: 99%
“…Another screening approach identified nine small-molecule inhibitors of RCE1, including NSC 1011, 73101, 295642, 321237, and 609974 [41]. Recently, it has been published that the anti-HIV protease inhibitors Ritonavir and Lopinavir can suppress RCE1 and CAAX Rab proteins, sensitizing the liver to organelle stress and injury [42].…”
Section: Targeting the Post-prenylation Caax Processingmentioning
confidence: 99%